Indicators of Fiscal Impulse for New Zealand - Renee Philip; John Janssen (New Zealand Government, The Treasury, 2002)
This paper defines fiscal impulse as a measure of whether government fiscal policy decisions are adding to, or subtracting from, aggregate demand pressures in the economy. When assessing the effects of fiscal policy on the economy it can be useful to have an approximate estimate of fiscal impulse. Estimates of fiscal impulse range from simple indicators based on fiscal aggregates, to more complicated approaches requiring greater use of judgement and economic theory. This paper develops reasonably simple indicators based on adjusted fiscal aggregates. It also sets out some sensitivity analysis. The indicators reflect intuitive assessments about changes in New Zealand fiscal policy over the last decade and looking forward into the forecast period. Although estimates are relatively insensitive to alternative assumptions, this is likely to be the result of the relative stability of the time period under consideration. Simple indicators of fiscal impulse have limitations. At best they can only provide an indication of the first round impact of changes in discretionary fiscal policy. A more complete assessment of the effects of fiscal policy on the economy requires a full-scale macroeconomic model, perhaps complemented with time series analysis.
Keywords: E62; H60; 330; Fiscal impulse; cyclical-adjustment; aggregate demand; New Zealand.